Desenvolvimento e avaliação de Scaffolds híbridos a base de colágeno contendo moléculas bioativas no reparo de feridas cutâneas - Rodrigues, Jéssica Peixoto (2022)
The development of dressings from biomaterials has been the subject of research due to their unique characteristics and capabilities. Animal origin hydrogels, such as collagen and chitosan, operate as promising materials for applications in injuries and chronic wounds, functioning as a repairing agent. The aim of this study is to evaluate the in vitro effects of scaffolds derived from collagen-rich biomaterials, with different formulations containing bioactives such as chitosan, NAC and ε-PL. A previously decellularized collagen-rich biomaterial was used to manufacture a scaffold made from a collagen hydrogel bioconjugated with chitosan by cross-linking using EDC/NHS and addition of NAC and ε-PL. Cell viability was verified by resazurin and live/dead assays, the ultrastructure of biomaterials was evaluated by SEM and FTIR. Antimicrobial sensitivity was assessed by antibiogram. The healing potential of the biomaterial was evaluated in vivo, in a model of healing of excisional wounds in mice. On the 7th day after the injury, the wounds and surrounding skin were collected, weighed and processed for evaluation of biochemical and histological parameters associated with inflammatory and angiogenic processes. The results showed higher cell viability when chitosan was cross-linked to the pre-gel, while commercial collagen maintained its cytocompatibility without chitosan. There was an increase in porosity after crosslinking, which was verified by covalent bonding in the stretching of the collagen bands and an antimicrobial action was observed by the formation of a halo in scaffolds containing NAC and ε-PL. Pre-gel scaffolds bioconjugated with chitosan and NAC/ε-PL improved tissue healing, with reduced lesion size, reduced inflammation and increased vascularity. It is concluded that collagen/pre-gel scaffolds cross-linked with chitosan-NAC-ε-PL have desirable characteristics for low-cost tissue repair and are promising biomaterials in the use of regenerative medicine.